Application of adipose-derived stem cells in ischemic heart disease: theory, potency, and advantage - Xiao, Weizhang; Shi, Jiahai (Frontiers in Cardiovascular Medicine, 2024)
Adipose-derived mesenchymal stem cells (ASCs) represent an innovative candidate to treat ischemic heart disease (IHD) due to their abundance, renewable sources, minor invasiveness to obtain, and no ethical limitations. Compared with other mesenchymal stem cells, ASCs have demonstrated great advantages, especially in the commercialization of stem cell-based therapy. Mechanistically, ASCs exert a cardioprotective effect not only through differentiation into functional cells but also via robust paracrine of various bioactive factors that promote angiogenesis and immunomodulation. Exosomes from ASCs also play an indispensable role in this process. However, due to the distinct biological functions of ASCs from different origins or donors with varing health statuses (such as aging, diabetes, or atherosclerosis), the heterogeneity of ASCs deserves more attention. This prompts scientists to select optimal donors for clinical applications. In addition, to overcome the primary obstacle of poor retention and low survival after transplantation, a variety of studies have been dedicated to the engineering of ASCs with biomaterials. Besides, clinical trials have confirmed the safety and efficacy of ASCs therapy in the context of heart failure or myocardial infarction. This article reviews the theory, efficacy, and advantages of ASCs-based therapy, the factors affecting ASCs function, heterogeneity, engineering strategies and clinical application of ASCs.